2022
DOI: 10.1080/22423982.2022.2055728
|View full text |Cite
|
Sign up to set email alerts
|

Cultural competence and safety in Circumpolar countries: an analysis of discourses in healthcare

Abstract: Circumpolar Indigenous populations continue to experience dramatic health inequities when compared to their national counterparts. The objectives of this study are first, to explore the space given in the existing literature to the concepts of cultural safety and cultural competence, as it relates to Indigenous peoples in Circumpolar contexts; and second, to document where innovations have emerged. We conducted a review of the English, Danish, Norwegian, Russian and Swedish Circumpolar health literature focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Patients from Greenland have the same access to specialised surgical treatment in Denmark as Danish patients [ 26 ]. Time from diagnosis and referral after MDT conference was not significantly different between the two groups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients from Greenland have the same access to specialised surgical treatment in Denmark as Danish patients [ 26 ]. Time from diagnosis and referral after MDT conference was not significantly different between the two groups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…55 73 74 Several literature reviews and at least ten additional PROS-PERO registrations address cultural safety. These reviews focus on describing culturally safe interventions for specific health issues, [9][10][11][12][13][14][15][16] how to improve healthcare practices (medicine, nursing, midwifery), [17][18][19][20][21][22][23] eHealth applications, 24 the presence of cultural safety in health research, 25 narrative descriptions of what cultural safety is [26][27][28][29][30][31][32] and the experiences of beneficiaries. 33 34 A limited literature on intercultural approaches to health emphasises communication issues.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Familiarity with cultural safety is growing in New Zealand, Australia, Canada and the USA. 28 In Latin America and Europe, interculturality is a more common and related concept. 59 69 Healthcare providers and governments have increasingly committed to integrating these principles into their services.…”
Section: Introductionmentioning
confidence: 99%
“…How could CS be translated into Korean contexts for equity, diversity, and inclusion? While most CS programs have targeted Indigenous Peoples in countries with colonial histories (Lavoie et al, 2022;Mehus et al, 2019;Pimentel et al, 2021;Pitama et al, 2018), literature has rarely reported on programs in countries that had been occupied, such as Korea. Some studies have documented a small number of Asian students' re ections (Plaisime et al, 2023), but their main focus was white/Black-based racism, which does not apply to Korean contexts.…”
Section: Introductionmentioning
confidence: 99%